Influence of Palladium Crystallite Size on the Course of the DENOX Reaction - Wiesława Ćwikła-Bundyra; Dobiesław Nazimek (Adsorption Science & Technology)
Catalysis is one of the important fields in the industry where small metal particles are applied. The effect of the metal crystallite size in the catalytic reduction process has investigated for palladium, the present paper reporting on the effect of the Pd dispersion on the course of the reaction between NO and CO. Such studies also allowed changes in the activity and selectivity of the process and the concentration of B 5 sites on the surface of Pd catalysts to be traced.